FACE: (New) Facets of a Sociopragmatic Concept - Held, Gudrun, (Language and Linguistics E-Books Online, Collection 2024., 2025)
Face has become a key-concept in current socio-pragmatics. By virtue of its metaphorical force, it enables researchers to explain universal processes of human communication mostly reflected in language use. Yet being an English construct, in intercultural comparison, face provokes critical debates putting in doubt namely its relation to im/politeness -theories. The 8 articles in this volume tie on these issues putting face under linguistic scrutiny: With different approaches and methods, some re-consider the notion of face comparing labels and expressions in lingua-cultures other than English; others explore the verbal enactment of face in selected speech acts, conversational moves and interactional settings.